Genomic analysis and comparison of very virulent infectious bursal disease virus (vvIBDV) affecting Malaysian poultry chickens with other IBDV strains - Ghazali, Mohd. Shahrin; Ahmad Raus, Raha; Mat Amin, Noriha; Shohaimi, Syamsiah Aini; Abu Bakar, Farah Diba; Zainuddin, Norafiza; Nor Muhammad, Nor Azlin Alia (Scholars Research Library, 2013)
IBDV outbreak had been reported to infect broiler chicken in Malaysia and cause high mortality. It had been reported that the virulence and pathogenicity of the virus is related to its coated protein, specifically the VP2 hypervariable regions. To study this, the nucleotides and protein of the local IBDV isolate was sequenced and analyzed by comparing it with other IBDV that had been reported previously. To obtain the virus sequence, local IBDV isolate strain 3529/92 was propagated in SPF eggs and RNA were extracted, amplify by rt (reverse transcriptase)-PCR before being inserted into pCR 2.1 TOPO for cloning and sequencing. The full length of the gene segment for the coat protein was constructed by concomitantly joining the fragments using the native restrictions sites of IBDV in pTrcHis2a expression vector. The sequence analysis revealed that the local IBDV strain 3529/92 consists of 3039 nucleotides which encodes for 1012 amino acids. BLAST analysis of the nucleotides sequence showed that the local strain shared greatest similarity with the Dutch D6948 vv IBDV subtypes. Analysis on the VP2 variable regions of 3529/92 showed most amino acid substitutions at VP2 variables regions are similar to the changes in VP2 variable regions of vvIBDV subtypes. Phylogenetic analysis prove that that 3529/92 isolates closely related with vvIBDV subtypes. The nucleotides sequences of ORF A2 3529/92 will give great insight in vaccine development against IBDV especially vvIBDV subtypes.